Salvation in the Gospel of Mark: the death of Jesus and the path of discipleship - Markusse-Overduin, Gabrielle (Pickwick Publications, 2018)
Introduction -- Implications of Mark's narrative structure -- The (im)possible path of discipleship -- The noble death and the emotions of Jesus -- The divine pathos -- Mark and martyrdom -- Mark's use of Isaiah's salvation narrative -- Mark's use of Daniel's One like a son of man -- Mark's use of Psalm 22's righteous sufferer -- Conclusions.